1999
DOI: 10.1053/cp.1999.v66.103402001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased platelet serotonin transporter sites and increased platelet inositol triphosphate levels in patients with unipolar depression: Effects of clomipramine and fluoxetine

Abstract: Drug-free patients with depression had simultaneously decreased 5-HT transporter (5-HTT) sites and overstimulated phosphoinositide signaling systems. Clomipramine and fluoxetine treatments, which further decreased the density of 5-HTT sites, allowed platelet inositol triphosphate levels to return to normal values only in responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 32 publications
7
54
0
Order By: Relevance
“…Moreover, increased IP 3 concentration has been reported in patients with unipolar depression (Alvarez et al, 1999). The lack of diagnostic and familial specificity of these findings could be interpreted as an indication of shared genetic factors in OCD and affective disorders.…”
Section: Diagnostic and Familial Specificitymentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, increased IP 3 concentration has been reported in patients with unipolar depression (Alvarez et al, 1999). The lack of diagnostic and familial specificity of these findings could be interpreted as an indication of shared genetic factors in OCD and affective disorders.…”
Section: Diagnostic and Familial Specificitymentioning
confidence: 96%
“…The decrease in whole blood 5-HT and 5-HTT binding are not unique to persons with OCD or at risk for developing such disorder, since these disturbances have also been observed in patients with affective disorders (Cleare, 1997;Alvarez et al, 1999) and in their unaffected relatives . Moreover, increased IP 3 concentration has been reported in patients with unipolar depression (Alvarez et al, 1999).…”
Section: Diagnostic and Familial Specificitymentioning
confidence: 97%
“…43 Changes in platelet 5-HT and SERT have been suggested as possible biomarkers for psychiatric illness (for review see Plein and Berk 44 ). Interestingly, Alvarez et al 45 reported a decrease in platelet SERT binding sites in depressed versus healthy individuals that was further reduced following 12-week administration of clomip ramine or fl uoxetine. Furthermore, a greater drop in platelet SERT binding sites was evident in antidepressant treatment responders versus nonresponders.…”
Section: Effects Of Chronic Antidepressant Exposure On Sertmentioning
confidence: 99%
“…Pandey et al (1999) found significantly lower PI-PLC activity and expression of the PLC isozyme PLC b1 in the brains of teenage suicide subjects relative to normal controls. In contrast, hyperactive PI signaling has been shown in platelets from depressed patients (Karege et al, 1996;Alvarez et al, 1999;Pandey et al, 2001). Elevated 5-HT-stimulated intracellular calcium has also been reported in platelets from unipolar depression (Delisi et al, 1998) and bipolar disorder (Suzuki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%